Do light-emitting diode cap lamps enable improvements in miner safety? - J. Sammarco (The National Institute for Occupational Safety and Health (NIOSH), 2009)
Proper illumination is critical to a miner?s ability to detect hazards in underground mines. Moving hazards are often located in the miner?s peripheral field-of-view, while slip/trip/ fall hazards are often located in the forward field-of-view. The objective of the research described in this paper was to determine if light-emitting diodes (LEDs) improve visual performance as compared to traditional incandescent (INC) cap lamps. The research presented focuses on comparative studies of a National Institute for Occupational Safety and Health (NIOSH) prototype LED, a commercial LED and an INC camp lamp. Thirty subjects participated in these studies, with ten subjects in each of the following age groups: 18 to 25 years, 40 to 50 years and 51+ years old. Visual performance was quantified by the subjects? speed and accuracy in detecting hazards, while visual performance for disability glare was quantified by the use of contrast sensitivity tests. Results suggest that LEDs with a visible spectrum containing a higher concentration of the shorter wavelengths can enable visual performance improvements with respect to disability glare, the detection of moving hazards in the peripheral field-of-view and the detection of floor hazards in the forward field-of-view. The NIOSH prototype LED cap lamp provided the best visual performance improvements for the older age groups in every test.